2019
DOI: 10.1108/bfj-11-2018-0780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the shelf-life extension of fresh-cut pineapple (Smooth cayenne) by application of different edible coatings

Abstract: Purpose The purpose of this paper is to evaluate the shelf-life of minimally processed pineapple when subjected to the use of different edible coatings. Design/methodology/approach The pineapples were peeled and cut into cubes. The gums were prepared by dissolving them in distilled water and then heated to total dissolution. After calcium chloride, citric acid and ascorbic acid and glycerol were added in the solutions. The pieces of pineapple were completely submerged in the respective solutions and then dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
(41 reference statements)
1
8
0
5
Order By: Relevance
“…A large number of recent articles have highlighted the advantages of using pectin over conventional polymers. Therefore, pectin is increasingly important for a multitude of food packaging applications, such as a thickening and gelling agent, colloidal stabilizer, texturizer, and emulsifier [16][17][18], a coating on fresh and cut fruits or vegetables [19][20][21] and as micro and nano-encapsulating agent for the controlled release of active principles with different functionalities [22]. Rodsamran et al [16] reported that bioactive pectin films can retard soybean oil oxidation during 30 days of storage.…”
Section: Pectin Structurementioning
confidence: 99%
“…A large number of recent articles have highlighted the advantages of using pectin over conventional polymers. Therefore, pectin is increasingly important for a multitude of food packaging applications, such as a thickening and gelling agent, colloidal stabilizer, texturizer, and emulsifier [16][17][18], a coating on fresh and cut fruits or vegetables [19][20][21] and as micro and nano-encapsulating agent for the controlled release of active principles with different functionalities [22]. Rodsamran et al [16] reported that bioactive pectin films can retard soybean oil oxidation during 30 days of storage.…”
Section: Pectin Structurementioning
confidence: 99%
“…Overall, these results suggest that the use of sodium alginate coatings for the preservation of fresh-cut pineapple is a promising strategy that could find useful applications in postharvest technology. AlgNa+AA AlgNa Control pineapple cultivars (Dussan-Sarria et al, 2014;Pizato et al, 2019), and different behaviors have been observed in the soluble solid content of cut pineapple samples during refrigerated storage. For instance, Pizato et al (2013Pizato et al ( , 2019, who worked with minimally processed peaches and pineapples, observed an increase in the soluble solid content of fruits with the passing of storage days.…”
Section: Discussionmentioning
confidence: 99%
“…AlgNa+AA AlgNa Control pineapple cultivars (Dussan-Sarria et al, 2014;Pizato et al, 2019), and different behaviors have been observed in the soluble solid content of cut pineapple samples during refrigerated storage. For instance, Pizato et al (2013Pizato et al ( , 2019, who worked with minimally processed peaches and pineapples, observed an increase in the soluble solid content of fruits with the passing of storage days. This result was attributed to the significant water loss suffered by the fruit, resulting in a concentration of total soluble solids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O uso de revestimentos comestíveis com propriedades físicas, sensoriais e microbiológicas desejáveis para frutas e vegetais minimamente processados pode reduzir alterações prejudiciais e, consequentemente, estender sua vida útil (YOUSUF et al, 2018). Alguns pesquisadores estudaram o efeito de diferentes tipos de revestimentos em várias frutas minimamente processadas, como mamão (HOLSBACH et al, 2019), melão (CHEVALIER et al, 2016), goiaba (ARROYO et al, 2020;COSTA et al, 2017), abacaxi (PIZATO et al, 2019;PADRÓN-MEDEROS et al, 2020;PRAKASH et al, 2020;BASAGLIA et al, 2021), brócolis (Pizato et al, 2020). A aplicação de quitosana comestível e revestimentos à base de xantana é uma alternativa viável para prolongar a vida útil de frutas e vegetais minimamente processados (PIZATO et al, 2020).…”
Section: Introductionunclassified